Post-processing Techniques in Antenna Measurement - Sierra Castaner, Manuel; Foged, Lars J. (Electromagnetic waves., 2019)
The following topics are discussed the introduction to antenna measurement and post-processing techniques, Source reconstruction using equivalent currents, Antenna and measurement improvements based on equivalent currents reconstruction, Holographic techniques to improve antenna measurements, Antenna measurement improvement using spherical or cylindrical mode expansion, Phase recovery in antenna measurements, Link between simulation and measurements and the future trends in antenna measurements.